SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI KEJAKSAAN TINGGI JAMBI - Louis, Ahmad; Elzas, Elzas (FORTECH (Journal of Information Technology), 2024)
The web-based library program using Senayan Library Management System (SLiMS) at the High Prosecutor's Office in Jambi aims to enhance the efficiency and accessibility of library collection management. SLiMS is an open-source software that provides various features for library management, including cataloging, circulation, inventory, and reporting. This implementation allows users to search for and borrow books online, facilitates library staff in managing collections, and provides accurate and real-time data on collection status. The system is expected to improve the quality of library services and meet the information needs of employees and the surrounding community. This research uses a descriptive method